SISTEM INFORMASI PENGELOLAHAN DATA OPERASIONAL KEGIATAN MEDIA BERITA PADA LEMBAGA RADIO REPUBLIK INDONESIA (RRI) JAMBI BERBASISI WEB: MySql, Laravel, Filament, Tailwind CSS, Visual Studio Code, Radio Republik Indonesia (RRI) Jambi - Limia Budiarti, Rike; Marsa Juleha (FORTECH (Journal of Information Technology), 2025)
Radio Republik Indonesia (RRI) is a Public Broadcasting Institution which organizes radio activities that are independent, neutral and function to provide information services, education, healthy entertainment, social control and social glue as well as preserving the nation's culture for the benefit of all levels of society through the implementation of radio broadcasting that reaching the entire territory of the Unitary State of the Republic of Indonesia. The aim of this research is to develop a system in the form of information, more precisely an information system, which aims to provide information related to RRI that can be known by the public or radio listeners on RRI. Of course, this information system is newer and its appearance can really attract public attention, more so than the previous RRI website. In the future, this information system can be used by RRI as an information system media and of course it can be further developed in the future. The collected data was analyzed using the web using the PHP programming language. PHP is a server-side language that is integrated with HTML, to create dynamic web pages, one of its functions is to receive, process and display data on a site, the data received will be processed in a database server program, then the results are displayed back on the browser screen. a site.